Faktor-faktor yang memengaruhi pengalaman merek ramah lingkungan dan dampaknya pada intensi perilaku konsumen hijau - Asan, Sucipto; Antonio, Ferdi (Jurnal Manajemen Maranatha, 2023)
Researchers have worked hard for many years to investigate the factors that influence pro-environmental behavior and still found inconsistent result of the predictors. Therefore, there is a need to identify other potential environmental behavior predictors. The intention of this study is to investigate the drivers of green brand experience and its impact on pro-environmental behavioural intentions. This study analyzes 229 customers of green beauty and personal care brand in Indonesia using quantitative method with non-probability purposive sampling technique. This study found that only interactivity and green informativeness in social media marketing management activities have positive and significant influence on the green brand experience. While entertainment, customization, and WOM have entertainment, customization, and WOM insignificant influence. This study also found that green brand experience has positive and significantly influenced customer co-creation participation, repurchase, as well as green word of mouth intention. The findings contribute to the development theory of brand experience and Technologies for the Pro-Ecological Action Model. This study also contributes to the management of social media activities in enhancing green brand experience and promoting pro-environmental behavioural intentions that benefit both the brand and the environment.